Round the Fire Stories - Doyle, Arthur Conan, 1859-1930; Castaigne, J. André, 1861-1929 (Salt Lake City, UT : Project Gutenberg, 2017)
"Round the Fire Stories" by Arthur Conan Doyle is a collection of short stories written in the early 20th century. This anthology features tales that blend the grotesque and the terrible, effectively crafted for sharing on a chilly evening around a fire. The stories delve into various aspects of human experience and curiosity, hinting at macabre events and mysterious legacies. The opening of "Round the Fire Stories" introduces us to the character Lionel Dacre, a wealthy and eccentric collector of occult literature residing in Paris. A visit to his home leads to a curious examination of a leather funnel with a mysterious past, linked to the dark practices of historical torture. Dacre proposes an experiment involving the funnel, suggesting a connection to dreams and past horrors. The narrative sets up an air of suspense and reveals Dacre's intent to unearth the object s intriguing story through a shared experience with the narrator, paving the way for a chilling exploration of history and the unknown. (This is an automatically generated summary.)
The leather funnel -- The beetle hunter -- The man with the watches -- The pot of caviare -- The japanned box -- The black doctor -- Playing with fire -- The Jew's breastplate -- The lost special -- The club-footed grocer -- The sealed room -- The Brazilian cat -- The usher of Lea House School -- The brown hand -- The fiend of the cooperage -- Jelland's voyage -- B. 24.
Release date is 2017-02-04
E-text prepared by Richard Tonsing and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Horror tales, English; English fiction; Short stories, English